Banned from the Discourse: Race to the Top and the State of Texas’ exclusion of Welfare Recipients from Educational Policy Discourse - Michelle Johnson (Adult Education Research Conference, 2011)
This paper explores the tensions that exist between the espoused purpose of Race to the Top education reform and the state of Texas educational plans to enhance the state’s economy through increased education. We use Fairclough’s (1995) critical discourse analysis (CDA) as the basis of our analytical framework.